Sea Ice Dynamics Drive Benthic Microbial Communities in McMurdo Sound, Antarctica - Currie, Ashleigh A.; Marshall, Alexis J.; Lohrer, Andrew M.; Cummings, Vonda J.; Seabrook, Sarah; Cary, S. Craig (Frontiers in Microbiology, 2021)
Climate change is driving dramatic variability in sea ice dynamics, a key driver in polar marine ecosystems. Projected changes in Antarctica suggest that regional warming will force dramatic shifts in sea ice thickness and persistence, altering sea ice associated primary production and deposition to the seafloor. To improve our understanding of the impacts of sea ice change on benthic ecosystems, we directly compared the benthic microbial communities underlying first-year sea ice (FYI) and multi-year sea ice (MYI). Using two tractable coastal habitats in McMurdo Sound, Antarctica where FYI (Cape Evans) and MYI (New Harbour) prevail, we show that the structure and composition of the benthic microbial communities reflect the legacy of sea ice dynamics. At Cape Evans, an enrichment of known heterotrophic algal polysaccharide degrading taxa (e.g. Flavobacteriaceae, unclassified Gammaproteobacteria, and Rubritaleaceae) and sulfate-reducing bacteria (e.g. Desulfocapsaceae) correlated with comparatively higher chlorophyll a (14.2 ± 0.8 μg gˉ1) and total organic carbon content (0.33% ± 0.04), reflecting increased productivity and seafloor deposition beneath FYI. Conversely, at New Harbour, an enrichment of known archaeal (e.g. Nitrosopumilaceae) and bacterial (e.g. Woeseiaceae and Nitrospiraceae) chemoautotrophs were common in sediments with considerably lower chlorophyll a (1.0 ± 0.24 μg gˉ1) and total organic carbon content (0.17% ± 0.01), reflecting restricted productivity beneath MYI. We also report evidence of a submarine discharge of sub-permafrost brine from Taylor Valley into New Harbour. By comparing our two study sites we show that, under current climate-warming scenarios, changes to sea ice productivity and seafloor deposition are likely to initiate major shifts in benthic microbial communities, with heterotrophic organic matter degradation processes becoming increasingly important. This study provides the first assessment of how legacy sea ice conditions influence benthic microbial communities in Antarctica, contributing insight into sea ice-benthic coupling and ecosystem functioning in a polar environment.